Characterization of The wave field along the Tróia-Sines embayed coast during a storm event. - Mota, Paul (2010)
The study of storm events is essential to understand and predict their effects on sandy beaches with implications for coastal management. Erosion due to storms is responsible for large changes in the shape of the beach profiles. The main goal of this work is the characterization of the wave field along the Tróia-Sines Embayed Coast (TSEC) during a storm event that occurred from 20 to 25 October 1999. The wave pattern along the TSEC was evaluated using the SWAN and Méso-NH models. The results showed the shadowing effect of the Espichel Cape in the northern part of the TSEC, the influence of the Setúbal canyon in the middle and of the Sines Cape in the southern sector of TSEC. Under NW storm conditions and SW wind the relative influence of the sea on wave field increases northwards, with a decreasing of the wave height in the same direction.